Perceived School Climate and Students' Mental Health - Naeimeh Kohoulat; Mohammad Reza Dehghani; Najmeh Kohoulat (Shiraz University of Medical Sciences, 2015)
Background: School climate has been linked with improved academic achievement, reduced behavioral problems and increased students' health, especially mental health. So this concept is often a target of school improvement initiatives. Objectives: The goal of this study was to determine the effect of school climate on elementary students' mental health. Patients and Methods: The study comprised 300 grade 6 elementary school students in Shiraz , including 165 girls and 135 boys selected through multi-stages cluster random sampling. During a 45-min school session, the students completed a self-report questionnaires tapping school climate survey provided by Haynes and his colleagues in 2001 and also the general health questionnaire developed by Goldberg in 1978. All descriptive statistics, regression and confirmatory factor analyses, were performed using SPSS 19. Results: Simultaneous multiple regression of school climate on students' mental health showed that except for building appearance, other dimensions of school climate were predictors of elementary students' mental health. Conclusions: According to our findings, it seems that school climate plays a critical role in student's mental health. In fact caring for and supportive school environment can promote well-being and students' mental health.